Injection-Based Management of Osteoarthritis of the Knee: A Systematic Review of Guidelines - Pavone, Vito; Vescio, Andrea; Turchetta, Matteo; Giardina, Serena Maria Chiara; Culmone, Annalisa; Testa, Gianluca (Frontiers in Pharmacology, 2021)
Osteoarthritis (OA) is a leading cause of disability among older adults. Numerous pharmaceutical and nonpharmaceutical interventions have been described. Intra-articular injections are commonly the first line treatment. There are several articles, reporting the outcome of corticosteroids (CS), hyaluronic acid (HA) and platelet rich plasma (PRP). The aim of the study is to highlight the usefulness, indication and efficacy of the intra-articular injection of principal drugs. CSs have been shown to reduce the severity of pain, but care should be taken with repeated injections because of potential harm. HA reported good outcomes both for pain reduction and functional improvement. Different national societies guidelines do not recommend the PRP intra-articular injection in the management of knee OA for lack of evidence. In conclusion, the authors affirm that there is some evidence that intra-articular steroids are efficacious, but their benefit may be relatively short lived (<4 weeks). Most of the positive outcome were limited to the studies or part of the studies that considered the injection of high molecular weight as visco-supplementation, with a course of two to four injections a year.